(untitled) (Observatorio Económico, 2017)
The Real Academia Española (RAE) defines "segregation" as "to separate or set apart something or someone from another thing or things." Given this definition, segregation would be worrying when it exists on the basis of socioeconomic factors such as income, race, sex, etc. Indeed, the RAE offers a second definition: "to separate and marginalize a person or a group of people for social, political, or cultural reasons." Continue reading...